(untitled) (Indian Journal of Animal Production and Management, 2016)
An experiment was conducted to study the effect of probiotics supplementation and tanniferous diet inclusion on health status by estimating the hematological and biochemical diagnostic parameters in Deccani ram lambs. 18 Deccani ram lambs of uniform body weight (16.5±0.64 kg) were randomly allotted to 3 groups in a completely randomized design. The dietary treatments were viz., T1: Basal diet (chopped sorgum stover + chopped green fodder as roughage source) + group 1 concentrate, T2: Basal Diet + Group 2 concentrate (with horse gram), T3: Basal diet + Group 3 concentrate supplemented with probiotics @ 4kg per100kg concentrate. Deccani ram lambs were fed the respective diets ad lib. to meet the nutrient requirements throughout 90 days of feeding trial. Blood glucose concentration was comparable among the experimental groups, however relatively higher (P<0.05) total proteins, cholesterol, albumin and globulin concentration in blood serum was observed with probiotic supplementation and horse gram inclusion. Significant (P<0.05) increase in the mean serum liver enzymatic activities was observed in growing Deccani ram lambs during experimentation than before start of experiment. Serum cobalt, copper, zinc, iron, magnesium and manganese values were comparable among the experimental groups, however a significant (P<0.05) increase was observed in the mean mineral values in growing Deccani ram lambs during experimentation than before start of experiment. It may be concluded that, inclusion of tanniferous protein had no detrimental effect on health as reflected in serum metabolites and serum minerals.